The Use of a Wearable Camera, SenseCam, as a Pictorial Diary to Improve Autobiographical Memory in a Patient with Severe Memory Impairment - Berry, Emma; Browne, Georgina; Kapur, Narinder; Hodges, Steve; Smyth, Gavin; Williams, Lyndsay; Conway, Martin; Wood, Ken (Microsoft Research, 2006)
Results from patient’s point of view: ‘It has enormous potential as a memory aid and has been a great success for us personally’ More relaxed socially and less anxious Sharing experiences again was a ‘sheer pleasure’ Seeing images brings memories ‘flooding back
Presentation at the Memories for Life Colloquium: the future of our pasts, British Library Conference Centre, London, December 2006